University Student Perceptions of Online Learning in Jordan - Alkhawaldeh, Khleef; Eldurini, Sarah; Alrai, Dima; Yaghmourian, Sara (Journal of University Teaching and Learning Practice, 2023)
This research paper examined Jordanian university students’ perceptions of online learning in terms of knowledge, attitude, and practice (variables of the KAP model). It also investigated the relationship between their perceptions of online learning and their academic performance. students’ perceptions of variables of the KAP model toward online learning were measured through an online questionnaire distributed to Jordanian universities students. Academic performance was also measured by identifying students’ perceptions of their academic performance after switching to online learning due to COVID-19. One-sample t-test results indicated that the means of responses fall within the area of agreement (agree and strongly agree) regarding students’ perceptions of online learning in terms of knowledge, attitudes, and performance without any significant differences. Correlation and regression analysis showed statistically significant relationships between students’ perceptions of their knowledge, attitudes and practices toward online learning and their academic performance. Such a positive perception of students towards online learning can be implied by educational institutions and educators to put the best use of online learning as a starting point to complement traditional face-to-face teaching by investing in technologies that support online learning, and by enhancing and improving online platforms to deliver course materials, provide additional resources, and facilitate discussions and collaboration among students in a more effective, efficient way.